Supreme Court's Legal Advice: Limits, Procedures, and Need for Change - Iswandi, Kelik (Jurnal Hukum dan Peradilan, 2024)
The Supreme Court offers legal advice to state organs and government agencies. Nonetheless, there are no regulations governing the execution of Supreme Court Legal Advice. This paper analyses the limitations and procedures of Supreme Court legal advice. This is a normative legal analysis grounded in conceptual and statutory law. This study utilized legal texts, doctrinal sources, and scientific material. This study employs Miles and Huberman's data analysis methodology. This study demonstrates that Article 37 of the 1985 Supreme Court Law and Article 22 paragraph (1) of the 2009 Judicial Power Law are contradictory. The dispute pertains to the petitioner seeking Supreme Court Legal Advice. The Supreme Court's Legal Advice is only extended to state organs and government agencies. The Supreme Court lacks the authority to offer legal advice to local governments, community organizations, and non-governmental organizations. The Chief Justice of the Supreme Court offers legal advice to state organs, while the Chairman of the Supreme Court Chamber provides legal advice to government agencies. Both legal advice continues to be designated as Supreme Court Legal Advice.